Community-based participatory action research on rheumatic heart disease in an Australian Aboriginal homeland: Evaluation of the 'On track watch' project. (June 2019) - Haynes, Emma; Marawili, Minitja; Marika, Brendan Makungun; Mitchell, Alice G.; Phillips, Jodi; Bessarab, Dawn; Walker, Roz; Cook, Jeff; Ralph, Anna P.
Highlights: Knowledge gained through reciprocal knowledge co-creation was relevant and valued. Research achieves strong impacts when community identify and implement priorities. Traditional Aboriginal approaches to learning, such as metaphor, must be prioritised. This research has influenced change in RHD Australia policy at the national level. Recommendation: shift focus from 'self-management' to 'group/community care'. Abstract: Strategies to date have been ineffective in reducing high rates of rheumatic heart disease (RHD) in Australian Aboriginal people; a disease caused by streptococcal infections. A remote Aboriginal community initiated a collaboration to work towards elimination of RHD. Based in 'both-way learning' (reciprocal knowledge co-creation), the aim of this study was to co-design, implement and evaluate community-based participatory action research (CBPAR) to achieve this vision. Activities related to understanding and addressing RHD social determinants were delivered through an accredited course adapted to meet learner and project needs. Theory-driven evaluation linking CBPAR to empowerment was applied. Data collection comprised focus groups, interviews, observation, and co-development and use of measurement tools such as surveys. Data analysis utilised process indicators from national guidelines for Aboriginal health research, and outcome indicators derived from the Wallerstein framework. Findings include the importance of valuing traditional knowledges and ways of learning such as locally-meaningful metaphors to explore unfamiliar concepts; empowerment through critical thinking and community ownership of knowledge about RHD and research; providing practical guidance in implementing empowering and decolonising principles / theories. Lessons learned are applicable to next stages of the RHD elimination strategy which must include scale-up of community leadership in research agenda-setting and implementation.